Evaluating the Usability, Perceived Performance, and Perceived Effects of KBGAN iHealth© and KBGAN iFeed© Mobile Apps for Buffalo Management in Selected Municipalities in the Philippines - Palacpac, Eric Parala; Pacsa Balingit, Kae Ann Marie; Dinulos Bonifacio, Airon Andrew; Villanueva, Marvin Ardeza; Tolentino, Randolph Bautista; Uy-DeGuia, Mary Rose De Leon; Tolentino Llantada, Phoebe Lyndia; Castillo, Charity Ignacio; Brul, Beverly Janabajal; Adecer Rubio, Hannah Carmela; Abes, Maica Miclat (Journal of Buffalo Science, 2024)
This study evaluates the KBGAN iHealth© and KBGAN iFeed© mobile apps designed for buffalo health and feeding management, particularly for agricultural extension professionals (AEPs) in selected Philippine municipalities. These apps aim to address challenges in buffalo management, such as limited access to veterinary expertise, personalized recommendations, organized data, communication channels, and difficulties in calculating ideal feed compositions and meeting the distinct needs of smallholder farmers and AEPs. Despite System Usability Scale (SUS) scores indicating marginal acceptability for both apps, weighted mean scores by AEPs for statements assessed on a 5-point Likert scale (1 as strongly disagree and 5 as strongly agree), demonstrate that AEPs reported high confidence in the accuracy of buffalo health diagnostics (Mean of 4.20) and health management recommendations (Mean of 4.17) provided by KBGAN iHealth©. Similarly, KBGAN iFeed© received favorable ratings, with AEPs expressing agreement on the accuracy of feeding recommendations (Mean of 3.89) and the facilitation of feeding ration computations (Mean of 4.00). These positive perceived performance outcomes, coupled with increased confidence (Mean of 4.03) and motivation (Mean of 4.00) among AEPs, suggest the potential for frequent and consistent app usage despite usability concerns. Chi-square tests examining the relationship between AEP characteristics and SUS scores for the apps reveal significant associations between AEPs' education and experience levels and SUS scores for KBGAN iFeed©. The choice of IT device also influences KBGAN iHealth© SUS scores. Proposed enhancements by AEPs include refining algorithms, improving the user interface for navigation, speed, and efficiency, and incorporating features such as photo uploads and geotagging.